Clinical profile of hemodialysis patients attending a tertiary care hospital in Delhi, India - Kumar, Mithilesh; Saini, Shipra; Parashar, Lokesh; Chetiwal, Rajesh; Kalra, Tanisha; Kalra, Nikhita (International Journal Of Community Medicine And Public Health, 2021)
Background: CKD (chronic kidney disease) is one of the major complications of diabetes and hypertension. With increase in prevalence of non-communicable diseases, the patients presenting with the symptoms of CKD are also rising. Most of the patients suffering from CKD eventually land up on renal replacement therapy, putting extra burden economically as well as psychologically to the self and their family. The aim of the study is to find out the socio demographic and clinical profile of the patients suffering from CKD attending a tertiary care hospital in Delhi. Methods: It was a record based descriptive analysis, conducted between January 2019 and June 2019 in one of the ESIC (Employee State Insurance Corporation) hospital of Delhi. Medical Records of the only those patients were considered whose complete data were present in the record file. Data about Socio demographic profiles , clinical data, duration of CKD, duration of haemodialysis, viral markers, number of blood transfusions, vascular access, number of failed AV fistula etc. were entered in MS Excel and analysed through SPSS 11. Results: Hospital records of 473 CKD patients undergoing hemodialysis were analyzed. It was found that 315 (67%) were males and 158 (33%) were females. Majority of the patients i.e. 245 were in the age group of 41-60 years followed by 166 who were in the age group of 21 to 40. Out of total patients, 195 (41.2%) participants were undergoing hemodialysis twice a week, 276 (58.4%) thrice a week, 2 (0.4) patients were undergoing hemodialysis session four times a week. Majority of the participants i.e. 414 (88%) were Hindu. Out of total 473 participants, 439 (93%) participants had sero negative for viral marker (i.e. HbsAg, HCV, HIV I and II) and 33 (7%) participants were sero positive for viral marker. Most common etiology of CKD was found to be hypertension in our study followed by diabetes. Conclusions: Patients suffering from chronic kidney diseases are increasing day by day with increasing prevalence of hypertension. Most of the patients of CKD patients were middle aged males. Most of the patients have to visit 3 times a week to any health care institution for hemodialysis. Many of the patients are getting infected with viral hepatitis during course of the illness.